Transmuted Alpha Power Inverse Rayleigh Distribution: Properties and Application - Malik, A. S.; Ahmad, S. P. (Journal of Scientific Research, 2019)
This paper proposes a new three parameter-distribution through the technique known as Transmutation. The proposed distribution is named Transmuted Alpha power inverse Rayleigh Distribution. Several important properties of the distribution are derived. The parameter estimation is also carried out. Two real life data set are used at the end to describe the potential application of proposed model.